INNOVATIVE METHODS OF DEVELOPING SENIOR STUDENTS’ READINESS FOR CAREER CHOICE - Khanifa Meilievna Berdieva (Western European Studies, 2025)
This article is devoted to exploring the specific and innovative forms of developing readiness among senior schoolchildren to make informed career choices. The author examines the psychological, pedagogical, and social factors influencing the process of vocational orientation during the final years of general education. Special attention is given to the current system of career guidance implemented within the preschool and school education framework of the Republic of Uzbekistan. The study highlights the importance of early professional awareness, the integration of modern technologies into career education, and the role of teachers and parents in shaping students’ aspirations. Additionally, the article discusses methodological approaches and strategies aimed at aligning students’ personal interests and abilities with the labor market demands
Keywords: career guidance; professional orientation; education system